Harnessing 'Blue energy': A Review on Techniques and Preliminary Analysis - Md Hasan, K.N. (EDP Sciences, 2017)
Energy harvesting from the ocean called 'blue energy' began in the 1970's and should have reached its peak by today, but due to varying interests in the field and the growing potentials of other sources, its development was delayed. Recently, it receives more interest and a number of institutes has deployed their pilot plant. Blue energy is a type of renewable energy based on salinity gradient where power is generated from different salt concentration in saltwater (the ocean) and freshwater (river). When the mixing of seawater and freshwater occurs, an increase in the entropy of this system is observed and free energy is dissipated. This research aims to identify and compare existing techniques or methods of blue energy harvesting developed over time. Five different techniques were reviewed, looking at their principle of operation, configuration and performance. Based on the review, capacitive mixing method was selected for further analysis. Experiment was conducted to evaluate different factor including the concentration of sea water, volumes and type of electrodes. The highest output power obtained is 89.7 mW, while the average is about 30 mW. © The authors, published by EDP Sciences, 2017.